Improving the Laboratory Add-On Process and Increasing Housestaff Satisfaction with an EMR Intervention. Issue 1 (10th May 2016) - Shahnazarian, Vahe; Mehta, Parag
Abstract : At a community hospital in Brooklyn, New York, the process for ordering add-on testing to drawn blood tubes involved filling out a paper sheet, then faxing and bulleting that sheet to the lab. It was a very inefficient, cumbersome, and unsatisfactory way of completing the process. In light of this, an EMR intervention was implemented in which the add-on order was placed as an EMR order. The study spanned over almost five years, over a year of which was post-intervention. There was a statistically significant increase in the number of add-on orders being placed as a result of the intervention. This has greatly improved housestaff satisfaction with the overall process. In conclusion, the project was a great success and met its goals of simplifying a difficult and cumbersome process while increasing user satisfaction.